2017
DOI: 10.3389/fphys.2017.00903
|View full text |Cite
|
Sign up to set email alerts
|

Kir2.1-Nav1.5 Channel Complexes Are Differently Regulated than Kir2.1 and Nav1.5 Channels Alone

Abstract: Cardiac Kir2.1 and Nav1.5 channels generate the inward rectifier K+ (IK1) and the Na+ (INa) currents, respectively. There is a mutual interplay between the ventricular INa and IK1 densities, because Nav1.5 and Kir2.1 channels exhibit positive reciprocal modulation. Here we compared some of the biological properties of Nav1.5 and Kir2.1 channels when they are expressed together or separately to get further insights regarding their putative interaction. First we demonstrated by proximity ligation assays (PLAs) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 40 publications
4
40
2
Order By: Relevance
“…Interestingly, when a Nav1.5 mutant produces a DNE on Nav1.5, this does not necessarily imply that it concomitantly produces a DNE on Kir2.1/2.2 channels (p.D1690N) and vice versa (p.D1816VfsX7). This reinforces the contention that the biology of Nav1.5-Kir2.1 complexes differs somehow from that of each channel alone, even though the anterograde and retrograde trafficking routes of the complexes are similar to those of Nav1.5 channels alone (7).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Interestingly, when a Nav1.5 mutant produces a DNE on Nav1.5, this does not necessarily imply that it concomitantly produces a DNE on Kir2.1/2.2 channels (p.D1690N) and vice versa (p.D1816VfsX7). This reinforces the contention that the biology of Nav1.5-Kir2.1 complexes differs somehow from that of each channel alone, even though the anterograde and retrograde trafficking routes of the complexes are similar to those of Nav1.5 channels alone (7).…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, the results would indicate that, at least at some stages (biosynthesis and/or forward and retrograde trafficking), Nav1.5 and Kir2.1 proteins do interact, forming complexes. Indeed, previous results from our group demonstrated that at least a pool of Nav1.5 and Kir2.1 channels form complexes early after their synthesis at the ER (8) and that these complexes, whose cellular biology is regulated differently than that of Nav1.5 and Kir2.1 channels alone (7), exhibit preferential forward trafficking toward the membrane (7,8). Interestingly, when a Nav1.5 mutant produces a DNE on Nav1.5, this does not necessarily imply that it concomitantly produces a DNE on Kir2.1/2.2 channels (p.D1690N) and vice versa (p.D1816VfsX7).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, β1 is not the only interacting subunit and other auxiliary subunits of Nav1.5 (other β subunits and scaffolding proteins) are probably expressed in hSC-CM (Abriel, 2010). Furthermore, even other channels, such as the Kir2.1 K + channel, can form complexes with Nav1.5 (Willis et al, 2015;Utrilla et al, 2017;Ponce-Balbuena et al, 2018). As these subunits and interactions can modulate the response of Nav1.5, the expression of them in hSC-CMs most likely explains the observed difference in I Na kinetics between hSC-CMs and heterologous expressed Nav1.5+β1 (Figure 1).…”
Section: Drugmentioning
confidence: 99%
“…Since previous studies have shown that Na v 1.5 and K ir 2.1 have a parallelism in expression (Milstein et al, 2012;Utrilla et al, 2017; Ponce-Balbuena et al, 2018), we next explored whether the cell shape and size affect membrane localization and activity of Na v 1.5 channels by immunostaining and electrophysiological analysis, respectively. We found that, unlike K ir 2.1, Na v 1.5 exhibited no preferential localization in the corners versus edges of star-shaped Ex293 cells (Fig.…”
Section: Integrin Engagement Increases I K1 Density In Hek Cellsmentioning
confidence: 99%